STRATEGI PEMBELAJARAN AKHLAK DI TAMAN KANAK-KANAK TARBIAYATUL FURQAN KECAMATAN KANDANGAN - Salhah Salhah (EDUCATIONAL JOURNAL : General and Specific Research, 2023)
This research departs from the importance of a strategy used by the teacher in the teaching and learning process so that it can influence students to achieve learning objectives effectively and efficiently in creating expected learning situations and forming character and educating students to become faithful, noble, wholehearted, knowledgeable, capable, creative, independent, and become some religious children. This study aims to find out how the strategy of teaching morals is in the Kindergarten of Tardayatul Furqan, Kandangan District and what factors influence it. This research is a field research (field research). The subjects were 2 teachers and 59 children and the objects were moral learning strategies in Tarbiatul Furqan Kindergarten, Kandangan District and the influencing factors. To explore this research data, using interview techniques, observation and documentation. Through descriptive analysis techniques, this researcher produced the following findings: The strategies used by the teacher in learning Morals by Playing, Singing, Storytelling and Integrated. Influencing factors that influence moral learning strategies in Tarbiatul Furqan Kindergarten, Kandangan District, in terms of teacher factors, namely experience, level of education, supporting facilities, in terms of student factors, namely attention and interest in learning.